Do Glasses Modulate Age Perception?. (August 2020) - Brunet, Nicolas M.; Sharp, Jonathan
No formal studies have reported how glasses influence age perception, except for a London Vision Clinic survey that found that people over 45 look 5 or more years older when wearing eyeglasses. To investigate the effect of eyeglasses and sunglasses on age perception while controlling for age and interpersonal differences, we digitally manipulated the photographs of faces of 50 young adults, to create two age conditions (young and old) and three eyewear conditions (no glasses, eyeglasses, and sunglasses). Participants then estimated the age of the faces, displayed in random order. Contrary to the generally accepted beliefs that wearing eyeglasses makes you look older and wearing sunglasses make you look younger, our results suggest that the effect of glasses on age perception is rather small.